2004
DOI: 10.1074/jbc.m406999200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization, Chaperone Activity, and Nuclear Localization of p26, a Small Heat Shock Protein from Artemia franciscana

Abstract: Artemia franciscana embryos undergo encystment, developmental arrest and diapause, the last characterized by profound metabolic dormancy and extreme stress resistance. Encysted embryos contain an abundant small heat shock protein termed p26, a molecular chaperone that undoubtedly has an important role in development. To understand better the role of p26 in Artemia embryos, the structural and functional characteristics of full-length and truncated p26 expressed in Escherichia coli and COS-1 cells were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 59 publications
4
74
0
Order By: Relevance
“…p26, with a calculated monomeric molecular mass of 20.7 kDa, has an α-crystallin domain flanked by variable amino-and carboxyl-terminal regions, and it assembles into oligomers (Liang et al 1997a;Crack et al 2002;Sun et al 2004Sun et al , 2006Sun and MacRae 2005). Only diapause-destined Artemia embryos synthesize p26, and expression of the p26 gene is indifferent to heat in spite of possessing up-stream heat shock elements (Liang and MacRae 1999;Qiu et al 2006;Qiu and MacRae 2008a).…”
Section: Molecular Chaperones Diapause and Quiescence In Artemiamentioning
confidence: 99%
See 2 more Smart Citations
“…p26, with a calculated monomeric molecular mass of 20.7 kDa, has an α-crystallin domain flanked by variable amino-and carboxyl-terminal regions, and it assembles into oligomers (Liang et al 1997a;Crack et al 2002;Sun et al 2004Sun et al , 2006Sun and MacRae 2005). Only diapause-destined Artemia embryos synthesize p26, and expression of the p26 gene is indifferent to heat in spite of possessing up-stream heat shock elements (Liang and MacRae 1999;Qiu et al 2006;Qiu and MacRae 2008a).…”
Section: Molecular Chaperones Diapause and Quiescence In Artemiamentioning
confidence: 99%
“…Reversible translocation of p26 into nuclei occurs in cysts exposed to anoxia, heat, and acidic pH, and during entry into diapause (Clegg et al 1994(Clegg et al , 1995(Clegg et al , 2000Liang et al 1997b;Liang and MacRae 1999). p26, which locates to nuclei in transfected mammalian cells (Sun et al 2004, is thought to interact with Hsp70 and nuclear lamins in cyst nuclei, but has little effect on transcription Clegg 2001, 2002). Based on these findings, p26 was thought to act as a molecular chaperone, a conclusion bolstered by the observation that p26 purified from either A. franciscana (Liang et al 1997a;Day et al 2003) or transformed bacteria (Sun et al 2004Sun and MacRae 2005) prevents the denaturation of heated tubulin and citrate synthase, and insulin when exposed to dithiothreitol.…”
Section: Molecular Chaperones Diapause and Quiescence In Artemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate was incubated in a 50 mM Hepes-KOH (pH 8.0) buffer at 45°C with various concentrations of AtTDX. Thermal aggregation of the substrate was determined by monitoring the turbidity increase at A340 as described (14,32).…”
Section: Isolation Of Heat-stable Hmw Complex Proteins From Arabidopmentioning
confidence: 99%
“…After termination of diapause by certain environmental cues, the embryos resume development, given suitable environmental conditions (Abatzopoulos et al 2002). Although several molecules associated with diapause have been described, the identification of factors involved in diapause initiation is still in its infancy (Sun et al 2004;Viner and Clegg 2001;Sharon et al 2009). Recently, flow cytometry analysis revealed that the cells of encysted embryos are arrested at the G1/S stage (data not shown), which indicated a relationship between the induction of diapause and control of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%